CHINA’S SECURITY DIPLOMACY IN THE MIDDLE EAST: A GLOBAL POWER POLITICS PERSPECTIVE - Rimapradesi, Yulia; Setiawan, Roy (Department of International Relations Universitas Satya Negara Indonesia, 2026)
This study analyzes China’s security diplomacy in the Middle East from the perspective of global power politics. The study aims to explain how Beijing’s diplomatic engagement, particularly in conflict mediation and regional stabilization, serves as a strategy for expanding influence amid the redistribution of international power. The study employs a qualitative approach with a descriptive-analytical design based on a literature review, drawing on academic literature, policy documents, and international reports. The findings indicate that China’s security diplomacy does not rely on military intervention, but rather on a non-interventionist approach, multilateral legitimacy, and economic interdependence. The mediation of Saudi-Iranian normalization in 2023 reflects a dual strategy: maintaining energy stability while expanding China’s strategic position in the global contest. However, this increased role remains gradual and has not yet fully replaced the United States security dominance. This study concludes that China’s security diplomacy represents a new form of power politics in the geoeconomic era, in which diplomacy and development serve as the primary instruments in shaping an increasingly multipolar security order.